Studi Kasus Menurunnya Motivasi Belajar Murid Broken Home dan Upaya Penanganannya - Linda Bungin; Abdul Saman; Aswar Aswar (Jurnal Psikoedukasi dan Konseling, 2026)
This study analyzes the declining learning motivation of broken home student and efforts to handle it. The purpose of this study is to determine: (1) An overview of the declining learning motivation of broken home student, (2) The causes and psychological impacts of broken home student on the declining learning motivation, (3) Efforts to handle the declining learning motivation of broken home student. The approach used in this study is a qualitative approach with a clinical case study research type. The data sources in this study are the subject (MFR), MFR's classmates, School counselor, and homeroom teacher. The data collection used qualitative analysis of the Miles & Huberman model in the form of data reduction, data presentation and drawing conclusions. The results of the study showed that the decline in learning motivation of broken home students was influenced by: (1) Descriptions related to the decline in learning motivation of broken home students in the MFR subject, namely truancy and entering and leaving class during class hours, lack of enthusiasm in following lessons, changes in behavior such as apathy or indifference, and lack of attention and affection from parents for MFR subjects. (2) Factors that caused the decline in learning motivation of broken home students in the MFR subject were internal factors: disruption to learning routines, emotional instability and loss of sense of security, and decreased interest and curiosity. As for external factors: disharmonious family conditions, an unconducive home environment and lack of parental support, and peer influence. (3) Efforts made to address the problem of declining learning motivation in broken home students in the MFR subject were by applying cognitive restructuring techniques. The application of this technique had a positive impact in the form of increasing students' desire to learn, the emergence of self-confidence, and changes in attitudes that were more adaptive towards academic tasks.